Some Stationary Deformation Problems for Compound Shells of Revolution - Grigorenko, Yaroslav; Bespalova, Elena; Yaremchenko, Natalia (NTU "KhPI", 2016)
A common approach to solving stationary deformation problems for compound systems composed of shells of revolution with different geometry and structure is developed. The approach is based on the use of shell models with different level of rigor and of the general numerical-analytical technique for solving corresponding problems. The examples of studying the subcritical stress-strain state, vibrations, and dynamical instability of complex form systems are presented, features of their deformation are noted.
Keywords: compound systems; stationary deformation; common approach; analysis